Acidity and specific gravity of goat milk produced by a group of breeders from the Costa Rican Central Plateau. - Chacón Villalobos, Alejandro (2004)
The evaluation was conducted at the Alfredo VolioExperimental Station of the University of Costa Rica and atthe Dairy Processing Facility of the Costa Rican Associationof Goat Breeders (A.C.C.C) both located in Ochomogo,Cartago. Goat milk supplied by the seven producers wasevaluated from June 1st to December 31th of 2002. Weight,acidity expressed as Dornic units, and specific gravity of themilk brought to the facility by every producer were measureddaily. From the total data that was gathered, a characteristicvalue of 17,7 ± 0,3 ºD for acidity and 1,029 ± 0,002 forspecific gravity were determinated, both for a confidencelevel of 99%. ANOVA statistical essays were conductedfollowed by Scheffé post hoc test in order to study thevariation of acidity and specific gravity at different monthsfor all the data regardless of the producer. In the other handvariations on both parameters for each producer and amongthem over the moths were also studied by the statisticalmethodology mentioned above. The results obtained showedno significant differences in acidity for any of the evaluations(P≤0,05), however significant variations were detected forspecific gravity for the same set of tests. When correlated,specific gravity and acidity showed a very low correlationcoefficient of 0,03 which makes impossible to argue any sortof relation between both variables. The same happened whenthe weight of milk brought by every producer day by day wascorrelated with specific gravity (r = -0,67)